Riflessioni sulla Quarta Biennale Europea del Paesaggio - Maria Goula (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
Many questions come from the fourth Biennal of Landscape Architecture of Barcelona and the attempt to answer when the event appears too near: reflection on contents, on the results of Rosa Barba Prize, on a possible reading or emerging some tendencies in building landscape all over the Europe during the last four years. Really, as Maria Goula underlines, it is difficult to talk about tendencies regards to a very short time from the last Biennal: the issue of artifice, urban square and European identity, memory obsession and public works , are probably steady elements that characterize the European identity.